Core-edge 2D fluid modeling of full tokamak discharge with varying magnetic equilibrium: from WEST start-up to ramp-down. (1st August 2022) - Scotto d'Abusco, M.; Giorgiani, G.; Artaud, J.F.; Bufferand, H.; Ciraolo, G.; Ghendrih, P.; Serre, E.; Tamain, P.
Abstract: In the present work we investigate for the first time the 2D fluid transport of the plasma in WEST during an entire discharge from the start-up to the ramp-down (shot #54487). The evolution of density profile, electron and ion temperatures together with the experimental magnetic equilibrium, total current and gas-puff rate is investigated. Comparisons with the interferometry diagnostic show a remarkable overall qualitative agreement during the discharge that can be quantitative at some locations in the plasma core. If at the onset of the X -points during the ramp-up the electron heat flux is dominant at the target, present results show that the ion heat flux becomes dominant during the stationary phase of the discharge. Using a simple model for erosion, present results assess the tungsten sputtering due to deuterium ions during the start-up and ramp-up phases of the discharge and confirm the need to consider full discharge simulation to accurately treat the W source of contamination. This work also demonstrates the interest of developing magnetic equilibrium free solver including efficient time integration to step toward predictive capabilities in the future for fusion operation.